2007
DOI: 10.1111/j.1750-3841.2006.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Inhibits LPS‐Induced Proinflammatory Mediator Inducible Nitric Oxide Synthase in Mouse Macrophage Cells

Abstract: Lycopene is a fat-soluble red-orange carotenoid found primarily in tomatoes and tomato-derived products, including tomato sauce, tomato paste, and ketchup, and other dietary sources, including dried apricots, guava, watermelon, papaya, and pink grapefruit. In this study, we have demonstrated the molecular mechanism underlying the anti-inflammatory properties of lycopene using a mouse macrophage cell line (RAW 264.7). Treatment with lycopene (10 microM) inhibited lipopolysaccharide (LPS)-stimulated nitric oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…Lycopene reduces proinflammatory cytokine and chemokineexpressing macrophages (10), it protects cultured hippocampal neurons against Aβ and glutamate toxicity (11), it protects against microglial activation in focal cerebral ischemia in rats (7), and it attenuates cognition impairment in the elderly (12). Lycopene is an agent that may prove useful in managing neurodegenerative disorders because of its ability to cross the blood-brain barrier (BBB) (13) and its strong antioxidant properties (14). Furthermore, lycopene has been shown to reverse neurobehavioral deficits in rats (15).…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene reduces proinflammatory cytokine and chemokineexpressing macrophages (10), it protects cultured hippocampal neurons against Aβ and glutamate toxicity (11), it protects against microglial activation in focal cerebral ischemia in rats (7), and it attenuates cognition impairment in the elderly (12). Lycopene is an agent that may prove useful in managing neurodegenerative disorders because of its ability to cross the blood-brain barrier (BBB) (13) and its strong antioxidant properties (14). Furthermore, lycopene has been shown to reverse neurobehavioral deficits in rats (15).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier epidemiological studies showed that dietary intakes of tomatoes and tomato-based products containing lycopene have been associated with a reduced incidence of chronic diseases such as cardiovascular and cancer diseases in numerous studies [8][9][10][11]. Recent studies of lycopene have focused on its antioxidant properties, and its beneficial health effects on chronic diseases are due to these properties [12][13][14][15]. Furthermore, accumulating evidence suggests that other mechanisms such as modulation of intracellular gap junction communication, metabolic pathways and the immune system may also be involved in the antioxidant effects of lycopene [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary factors play a significant role in the initiation of innate immunity and cytokine secretion. Tomato derived compounds prevent degenerative disease by lessening the production of inflammatory mediators such as TNF-α (Riso et al, 2006) and Cox-2 catalyzes prostaglandin (Shen et al, 2007;Rafi et al, 2007;Liang et al, 1999). Neutrophil gene expression and the response to modulation with polyphenols has been described as a therapeutic approach for the treatment of chronic diseases and Cox-2 is an important target for polyphenolic agents derived from the diet (Plummer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of post harvest technologies when the plants are processed and/or cooked at optimal conditions for bioavailability of bioactive compounds require further study (Gahler et al, 2003;Shen et al, 2007;Basu and Imrhan, 2007;Rafi et al, 2007). Post harvest heat treatment of tomatoes affects fruit ripening and decay (Falik, 1993).…”
Section: Introductionmentioning
confidence: 99%